One‐Pot Conversion of Cyclohexane to Adipic Acid Using a µ4‐Oxido‐Copper Cluster as Catalyst Together with Hydrogen Peroxide. Issue 3 (10th January 2020) - Gawlig, Christopher; Schindler, Siegfried; Becker, Sabine
Abstract: Invited for the cover of this issue are the groups of Sabine Becker, Technische Universität Kaiserslautern, and Siegfried Schindler, Justus‐Liebig‐Universität Gießen, Germany. The cover image shows the one‐pot oxygenation of cyclohexane to yield adipic and glutaric acid under mild conditions with a µ4 ‐oxido copper cluster and H2 O2 as catalyst and oxidant, respectively. Abstract : To our surprise, we found out that most of the cyclohexane was not converted to those two compounds but further to adipic and glutaric acid, which was actually even more interesting … Read more about the story behind the cover in the Cover Profile and about the research itself in the Communication by S. Becker et al.